Tyrosine Kinase Inhibitors in pediatric chronic myeloid leukemia: a focused review of clinical trials - Ata, Fateen; Benkhadra, Maria; Ghasoub, Rola; Fernyhough, Liam J.; Omar, Nabil E.; Nashwan, Abdulqadir J.; Aldapt, Mahmood B.; Mushtaq, Kamran; Kassem, Nancy A.; Yassin, Mohamed A. (Frontiers in Oncology, 2023)
Tyrosine Kinase Inhibitors (TKIs) is revolutionizing the management of pediatric Chronic Myeloid Leukemia (CML), offering alternatives to Allogeneic Hematopoietic Stem Cell Transplantation (AHSCT). We conducted a comprehensive review of 16 Randomized Controlled Trials (RCTs) encompassing 887 pediatric CML patients treated with TKIs including Imatinib, Dasatinib, and Nilotinib. The median patient age ranged from 6.5 to 14 years, with a median white blood cell count of 234 x 10^9/uL, median hemoglobin level of 9.05 g/dL, and median platelet count of 431.5 x 10^9/µL. Imatinib seems to be predominant first line TKI, with the most extensive safety and efficacy data. BCR::ABL response rates below 10% ranged from 60% to 78%, CCyR at 24 months ranged from 62% to 94%, and PFS showed variability from 56.8% to 100%, albeit with differing analysis timepoints. The Safety profile of TKIs was consistent with the known safety profile in adults. With the availability of three TKIs as first line options, multiple factors should be considered when selecting first line TKI, including drug formulation, administration, comorbidities, and financial issues. Careful monitoring of adverse events, especially in growing children, should be considered in long term follow-up clinical trials.